Subjective Proximity to Green Spaces and Blood Pressure in Children and Adolescents: The CASPIAN-V Study. (11th December 2020) - Abbasi, Behzad; Pourmirzaei, Mohammadali; Hariri, Sanam; Heshmat, Ramin; Qorbani, Mostafa; Dadvand, Payam; Kelishadi, Roya
Abstract : Evidence favoring a beneficial association between greenness and blood pressure (BP) in adults is accumulating. However, children and adolescents have been understudied accordingly. Methodologically, the data on "exposure" to residential green spaces are commonly satellite-derived, including rare existing studies on the relationship between proximity to green spaces and BP in children. Despite perfectly obliterating subjective biases, remote sensing methods of greenness data collection fail to address pragmatic interaction with such settings. This study aimed to assess the relationship between subjective proximity to green spaces and average/elevated BP in children. Through our study, systolic and diastolic BPs of 12, 340 schoolchildren living in CASPIAN-V study areas were examined and recorded. We performed surveys to obtain the data on their proximity to green spaces, defined as having access to such spaces within a 15-minute walk from their homes. Linear mixed-effects models with BP as the outcome variable and the measure of exposure to green spaces as fixed-effect predictor were applied. The analysis was adjusted for several covariates. We found that perceived residential proximity to green spaces was associated with −0.08 mmHg (95% confidence intervals (CIs): −0.58, 0.41; p value = 0.72) reduction in systolic BP and −0.09 (95% CIs: −0.49, 0.31; p value = 0.66) reduction in diastolic BP. We also observed statistically nonsignificant odds ratio of 1.03 (95% CIs: 0.76, 1.39), 0.96 (95% CIs: 0.80, 1.16), and 0.98 (95% CIs: 0.82, 1.16) for isolated systolic/diastolic hypertension and hypertension, respectively. Our observations remained consistent after adjustment for height, parental employment, low birth weight, parental obesity, single parent, and breastfeeding. In conclusion, subjective proximity to green spaces might not be associated with a lower mean BP in children. Well-designed studies applying both subjective and objective data should be performed to elaborate on the relationship further.